Międzynarodowa umowa sprzedaży towarów według Konwencji wiedeńskiej jako część międzynarodowego prawa prywatnego sensu largo - Marak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Despite the development of new forms of exchange, contracts of sale have traditionally played ihe most important role in international trade and hence the need for unification of the law on sales contracts. The most important legal act in this respect is the Vienna Convention of 11th April 1980 concerning contracts for the international sale of goods. The Convention is applied to transactions involving legal systems of more than one state. Yet the Vienna Convention is not applied in internal legal systems of the Convention member states. The unified law is applied only to contracts of sale concluded in international trade, as long as it has not been excluded by the contracting parties. And the parties often exclude the above international convention because usually, the intention of the economically more powerful party will be to impose its internal law by including a provision that any matters not regulated in the contract will be governed by the law applicable to the registered office of such party (civil code and other applicable legislation). However, it does not have to be like that because the parties to the contract can: not choose any applicable law or, by imprecisely indicating that the applicable law will be the law of the given state they indicate the entire legal system of such state and consequently - even without being aware of it - they lead to the application of the Convention, or finally they may deliberately choose the Convention. The Convention aims to remove the collisions occurring among non-uniform legal standards included in the legal systems of various states. The Convention is intended to contribute to the development of international trade by providing simplification and standardization of formal and legal aspects of trade contracts. The parties to the contract do not need to know many different legal systems, but instead they can choose one comprehensive legal act. The Convention includes modern regulations concerning sales contracts meeting the requirements of international trade. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 191-210